EWOLUCJONISTYCZNA TEORIA KULTURY W ANTROPOLOGII SPOŁECZNEJ - Daszkiewicz, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The evolutionism was the first attempt to synthesize and build theory of the culture in cultural anthropology as a science. Later generations refer to this theoretical direction by making adjustments and additions. Evolutionists have given first attempt of theoretical approach. They envisioned the unity of human psyche and using comparative studies. They have developed a conceptual apparatus, which entered into the composition of each anthropologist (endo-and egzogamia, totemism, tabu, animism, mana, etc.). Today the evolutionism is rather a history of cultural anthropology.